Dead calm [videorecording (DVD)] - Noyce, Phillip; Neill, Sam; Kidman, Nicole, 1967-; Zane, Billy; Williams, Charles, 1909-1975 (Warner Home Video, 1999)
John and Rae Ingram rescue the only surviving crew member of a crippled schooner, only to find themselves the targets of a deranged killer.